Chemical and microbiological characteristics of mango silage (Mangifera indica L) inoculated with natural yogurt - Caicedo, Willan (2021)
The aim of this study was to evaluate the chemical and microbiological composition of rejected mango silage inoculated with natural yogurt for use in animal feed. In total, 25 plastic microsilos of 1 kg were elaborated and the pH, dry matter (DM), crude protein (PB), ash, ethereal extract (EE), nitrogen-free extract (ELN) and crude energy (EB) were determined, as well as the probable contamination with Escherichia coli, Clostridium spp and Salmonella sp. Samples were taken on days 1, 4, 8, 15, and 30 of the study. The pH was higher on day 1 and stable between day 4 and 30. On day 8 of fermentation a good content of DM, PB, ash, ELN, FB, EB and low level of EE was determined. free of the pathogens tested. The combination of chopped ripe mango fruit, mineral salt, molasses, calcium carbonate, and natural yogurt produced a silage feed with an acceptable nutritional value for feeding animals of zootechnical interest.